Meeting the Challenges of Secondary Education in Latin America and East Asia : Improving Efficiency and Resource Mobilization - di Gropello, Emanuela (Washington, DC: World Bank, 2012)
In a context of increased primary school enrollment rates, secondary education is appearing as the next big challenge for Latin American and East Asian countries. This report seeks to undertake a detailed diagnostic of secondary education in these two regions, understand some of the main constraints to the expansion and improvement of secondary education, and suggest policy options to address these constraints, with focus on policies that improve the mobilization and use of resources.